UJI VARIASI DOSIS PERASAN LENGKUAS (Alpinia galanga) TERHADAP PERTUMBUHAN KUMAN Staphylococcus aureus - Evy Ratnasari Ekawati; Prasetyo Handriyanto (Jurnal SainHealth, 2017)
Infections caused by Staphylococcus aureus if not handled effectively will be able to cause death human. Hasn’t been found effective antibacterial against Staphylococcus aureus. Antibacterial active compounds in the essential oil of ginger have the ability as an antimicrobial, so it can be used as an antibacterial. This study aims to determine effectiveness of the juice of galangal (Alpina galanga) to the growth of Staphylococcus aureus. This study was an experimental study using disc diffusion method. The juice galangal (Alpina galanga) used has dosage of 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90% and 100%. At dosage of 50% to 100% has the potential to inhibit the growth Staphylococcus aureus. Nonetheless, based on the statistical test dosage of 50%, 60%, 70%, and 80% was significantly different from dosage 90%, 100%, and positive control and negative control. Dosage 90% and 100% was not significantly different, making more used dosage 90% to accelerate the process of growth inhibition Staphylococcus aureus.